Warrior in the wind pipe: Round worm in airway causing difficult endo-tracheal intubation - Fernandes, Kavina; George, Peter; Venkatesha, Bannur M (Journal of Medicine, 2016)
Abstract not available J MEDICINE July 2016; 17 (2) : 130